MO‐Co@N‐Doped Carbon (M = Zn or Co): Vital Roles of Inactive Zn and Highly Efficient Activity toward Oxygen Reduction/Evolution Reactions for Rechargeable Zn–Air Battery - Chen, Biaohua; He, Xiaobo; Yin, Fengxiang; Wang, Hao; Liu, Di‐Jia; Shi, Ruixing; Chen, Jinnan; Yin, Hongwei (Advanced functional materials, 2017)
A highly efficient bifunctional oxygen catalyst is required for practical applications of fuel cells and metal–air batteries, as oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are their core electrode reactions. Here, the MO‐Co@N‐doped carbon (NC, M = Zn or Co) is developed as a highly active ORR/OER bifunctional catalyst via pyrolysis of a bimetal metal–organic framework containing Zn and Co, i.e., precursor (CoZn). The vital roles of inactive Zn in developing highly active bifunctional oxygen catalysts are unraveled. When the precursors include Zn, the surface contents of pyridinic N for ORR and the surface contents of Co–Nx and Co3+/Co2+ ratios for OER are enhanced, while the high specific surface areas, high porosity, and high electrochemical active surface areas are also achieved. Furthermore, the synergistic effects between Zn‐based and Co‐based species can promote the well growth of multiwalled carbon nanotubes (MWCNTs) at high pyrolysis temperatures (≥700 °C), which is favorable for charge transfer. The optimized CoZn‐NC‐700 shows the highly bifunctional ORR/OER activity and the excellent durability during the ORR/OER processes, even better than 20 wt% Pt/C (for ORR) and IrO2 (for OER). CoZn‐NC‐700 also exhibits the prominent Zn–air battery performance and even outperforms the mixture of 20 wt% Pt/C and IrO2. MO‐Co@N‐doped carbon (M = Zn or Co) are prepared by using a bimetal metal–organic framework (containing Zn and Co) as precursor, showing excellent activity (EORR − EOER ≈ 0.78 V) and durability toward both oxygen reduction and evolution reactions as well as prominent Zn–air battery performance. It is revealed that inactive Zn plays vital roles in developing these highly efficient bifunctional catalysts.